Preparation method of multistage submicron silicon lithium battery negative electrode material

By using polyvinyl alcohol condensate, ethyl cellulose and polydopamine in the micron silicon lithium battery anode material to form a porous structure, the performance degradation caused by volume expansion of micron silicon is solved, the connection stability and conductivity of the material are improved, and the connection stability and electrical conductivity of the material are achieved. Better cycle performance.

CN119230810AActive Publication Date: 2024-12-31SHAOXING INST OF QUALITY & TECH SUPERVISION & INSPECTION
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411510900.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2024-12-31
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

The existing micron silicon lithium-ion battery negative electrode materials have volume expansion problems during charging and discharging, resulting in material powdering and battery performance degradation, and nano-silicon production costs are high and the consistency is poor.

Method used

The conjugated double bond polymer brought by polyvinyl alcohol condensation is used to combine the barrier properties and dissolution properties of ethyl cellulose and the high-temperature carbonization properties of polydopamine to form an intermediate porous structure, stably linking the carbon shell with micron silicon, providing sufficient expansion space.

Benefits of technology

It solves the problems of material powdering and battery performance degradation caused by volume expansion of micron silicon, improves connection stability and conductivity, meets the expansion needs of micron silicon, and improves the cycle stability and performance of lithium battery negative electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005105429880000111
    Figure BDA0005105429880000111
Patent Text Reader

Abstract

The invention belongs to the technical field of lithium batteries, and particularly relates to a preparation method of a multistage submicron silicon lithium battery negative electrode material which takes micron silicon as an inner core, a polyvinyl alcohol polycondensate with a porous structure as a connecting layer and a polypyrrole-based carbon layer as a carbon shell. The inside of the polyvinyl alcohol polycondensate in the connecting layer is of a porous structure. The invention further provides a preparation method of the multistage submicron silicon lithium battery negative electrode material. The problems of material pulverization and battery performance reduction caused by volume expansion of existing micron silicon are solved, stable connection is formed by utilizing a conjugated double bond-containing polymer brought by polycondensation of polyvinyl alcohol, and an intermediate porous structure is formed by combining the barrier property and dissolution removal property of ethyl cellulose and the high-temperature carbonization property of polydopamine, so that the battery performance is improved. Not only is the connectivity of the carbon shell and the micron silicon ensured, but also enough space is provided to meet the expansion requirement of the micron silicon.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium batteries, and in particular relates to a method for preparing a multi-level sub-micron silicon lithium battery negative electrode material. Background Art

[0002] Silicon material is one of the most promising negative electrode materials for lithium-ion batteries. Compared with graphite negative electrodes and lithium metal negative electrodes, silicon negative electrodes have higher theoretical specific capacity, are not prone to lithium dendrite precipitation, and have good safety and stability. The current silicon materials are mainly micron silicon and nano silicon. Micron silicon negative electrode materials have serious volume expansion problems during the charging and discharging process, which can easily cause the material to pulverize and fall off, and reduce the battery cycle performance. Although nano silicon alleviates the volume expansion problem, it has problems such as high production cost, low vibration and poor consistency. Therefore, with the increasing demand for the application of silicon materials in lithium-ion batteries, the market is in urgent need of a silicon-based negative electrode material that has both volume expansion problems and cycle stability. Summary of the invention

[0003] In view of the problems in the prior art, the present invention provides a method for preparing a multi-level sub-micron silicon negative electrode material, which solves the problems of material pulverization and battery performance degradation caused by the volume expansion of the existing micron silicon. The conjugated double bond polymer brought by the polycondensation of polyvinyl alcohol is used to form a stable connection, and the barrier and dissolution removal properties of ethyl cellulose and the high-temperature carbonization of polydopamine are combined to form an intermediate porous structure, which not only ensures the connectivity between the carbon shell and the micron silicon, but also provides sufficient space to meet the expansion needs of the micron silicon.

[0004] In order to achieve the above technical objectives, the technical solution of the present invention is:

[0005] A method for preparing a multi-level sub-micron silicon negative electrode material comprises the following steps:

[0006] Step 1, put the micron silicon into an ethanol aqueous solution and stir for 20-30 minutes, filter and dry, add to a hydrochloric acid solution and stir evenly to obtain acid-washed micron silicon, then add the acid-washed micron silicon to a chlorogenic acid solution and ultrasonicate for 20-30 minutes, filter and dry to obtain chlorogenic acid-wrapped micron silicon; the mass ratio of the micron silicon to the ethanol aqueous solution is 1:(3-5), the volume proportion of ethanol in the ethanol aqueous solution is 50-70%, the stirring speed is 200-400r / min, the drying temperature is 80-90°C, the pH of the hydrochloric acid solution is 4-5, and the mass ratio of the hydrochloric acid solution to the micron silicon is (2-3): 1. The stirring speed for uniform stirring is 300-500r / min, the chlorogenic acid solution is a chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 100-200g / L, the frequency of the ultrasound is 70-90kHz, the temperature is 10-20°C; the temperature of the drying is 80-90°C; in this step, the surface of the micron silicon is cleaned with an ethanol aqueous solution, and after the surface is cleaned, it is immersed in a hydrochloric acid solution, and the inert layer on the surface of the micron silicon is removed by acid washing, thereby improving the surface activity of the micron silicon; the acid-washed micron silicon is ultrasonically treated in the chlorogenic acid ethanol solution to form a stable and non-dense surface film during drying;

[0007] Step 2, adding dopamine and ethyl cellulose to ether and stirring evenly, then adding chlorogenic acid-wrapped micron silicon and dropping a small amount of distilled water, ultrasonicating for 10-20 minutes and then stirring for 20-30 minutes, filtering and drying to obtain coated particles, the mass ratio of dopamine to ethyl cellulose is 1: (10-12), the concentration of ethyl cellulose in ether is 200-400g / L, the stirring speed for uniform stirring is 100-200r / min, the concentration of chlorogenic acid-wrapped micron silicon in ether is 50-100g / L, the frequency of the ultrasound is 70-90kHz, the temperature is 5-10°C; the stirring speed is 200-400r / min, and the drying temperature is 30-40°C; this step utilizes dopamine The insolubility of dopamine in ether and the dispersibility and solubility of ethyl cellulose in ether form a suspended dopamine dispersion. A small amount of distilled water is added during the addition of micron silicon. The distilled water contacts with dopamine and chlorogenic acid to activate the surface groups, thereby realizing the attraction of dopamine and chlorogenic acid. At the same time, ether and distilled water belong to a slightly soluble system. Under the action of ultrasound, distilled water will penetrate into the ether to form a slightly soluble system, ensuring that the distilled water is fully in contact with dopamine and chlorogenic acid, and that dopamine is fixed on the chlorogenic acid. Therefore, after the end of ultrasound and stirring, an ether wet film of dopamine and ethyl cellulose is formed on the surface of chlorogenic acid on the micron silicon, and the ether is removed by drying to form a mixed film of dopamine and ethyl cellulose. At this time, chlorogenic acid and dopamine form a composite surface film.

[0008] Step 3, spraying sodium hydroxide solution onto the surface of the coated particles and standing at a constant temperature for 2-3 hours to obtain polydopamine-ethylcellulose wrapped micron silicon, wherein the pH of the sodium hydroxide solution is 10-11, and the spraying amount is 0.2-0.4 mL / cm 2 , the temperature of the constant temperature static is 50-60°C; this step utilizes the distilled water molecules in the composite surface film to maintain a certain degree of surface film looseness, combined with the spray permeability of the sodium hydroxide solution itself, and the insolubility and chemical inertness of ethyl cellulose itself. Under the action of temperature, polydopamine forms self-polymerization under alkaline conditions, and forms a stable polydopamine-ethyl cellulose composite film on the chlorogenic acid surface of micron silicon;

[0009] Step 4, putting polydopamine-ethylcellulose wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine wrapped micron silicon, then putting it into polyvinyl alcohol phenol solution and standing at a constant temperature for 20-30 minutes, filtering and freeze-drying to obtain in-situ porous coated micron silicon, wherein the mass ratio of the polydopamine-ethylcellulose wrapped micron silicon to the ether is 1:(6-8), the stirring speed for even stirring is 200-400r / min, and the drying temperature is 30-40°C; the polyvinyl alcohol and phenol in the polyvinyl alcohol phenol solution The mass ratio of porous polydopamine-coated micron silicon and polyvinyl alcohol is 1:(12-15), the mass ratio of porous polydopamine-coated micron silicon and polyvinyl alcohol is 10:(1-1.3), the temperature of constant temperature standing is 80-90°C, and the temperature of freeze drying is -10°C; this step utilizes the solubility of ether in ethyl cellulose to achieve the removal of ethyl cellulose and the porosity of polydopamine; at the same time, the stable dissolution of polyvinyl alcohol in hot phenol and the insolubility of phenol in polydopamine are utilized to ensure that a layer of polyvinyl alcohol film is adsorbed on the surface of polydopamine, and the composite polydopamine-coated micron silicon is obtained by freeze drying;

[0010] Step 5, mixing ether and water and stirring them fully to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid, wherein the mass ratio of the ether to water is (101-5):1, the stirring speed is 100-200 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is (4-5):(0.3-0.5):1, the concentration of the ethyl cellulose in the ether is 20-25%, and the stirring speed is 300-500 r / min; this step utilizes the slight solubility and layering of ether and water to obtain an ether liquid containing saturated trace water; and utilizes the solubility of the pyrrole monomer, dopamine and ethyl cellulose in ether to form a stable solution;

[0011] Step 6: immerse the in-situ porous coated micron silicon in the viscous liquid and stir for 2-4 minutes, filter and dry, spray the surface with pyrrole monomer ether solution, and acid self-polymerize after deposition to obtain polypyrrole-wrapped micron silicon, wherein the mass ratio of the in-situ porous coated micron silicon to the viscous liquid is 1:(5-8), the stirring speed is 800-1000r / min, the drying temperature is 20-30°C, the mass ratio of the pyrrole monomer in the pyrrole monomer ether solution to the ether is 1:(2-3), and the deposition amount is 1-1.5mL / cm 2 The solvent for the acidic self-polymerization is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 40-50°C; this step forms a liquid film on the surface of the entire system by immersion, and the composite film is formed on the surface of the porous composite polydopamine film in combination with the viscosity of the viscous liquid itself and drying; after the pyrrole monomer is deposited, the acidic self-polymerization is carried out to form a polypyrrole outer layer doped with polydopamine on the outer surface of the micron silicon. During the preparation process, the water in the viscous liquid can slightly open the polyvinyl alcohol structure, thereby ensuring the penetration of dopamine, pyrrole and polyvinyl pyrrolidone, and achieving excellent stability;

[0012] Step 7, the polypyrrole wrapped micron silicon is subjected to constant temperature treatment for 30-60 minutes, and a multi-level sub-micron silicon lithium battery negative electrode material is obtained by carbonization treatment, the temperature of the constant temperature treatment is 250-260°C; the carbonization treatment is carried out under a nitrogen atmosphere, and the carbonization temperature is 500-520°C; this step uses the polyvinyl alcohol treated at a constant temperature to form a polymer containing conjugated double bonds through a condensation reaction, and then during the carbonization process, polydopamine, polypyrrole and ethyl cellulose are formed into a stable carbonization treatment, and chlorogenic acid and polydopamine are formed into an integrated carbonization treatment, ensuring that polydopamine and polyvinyl alcohol condensation polymer are stably connected to micron silicon. The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as the core, a porous structure of polyvinyl alcohol condensation polymer as the connecting layer, and a polypyrrole-based carbon layer as the carbon shell, and the polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

[0013] It can be seen from the above description that the present invention has the following advantages:

[0014] 1. The present invention solves the problems of material pulverization and battery performance degradation caused by the volume expansion of existing micron silicon. The conjugated double bond polymer brought by polycondensation of polyvinyl alcohol is used to form a stable connection. The barrier and dissolution removal properties of ethyl cellulose and the high-temperature carbonization of polydopamine are combined to form an intermediate porous structure, which not only ensures the connectivity between the carbon shell and the micron silicon, but also provides sufficient space to meet the expansion needs of the micron silicon.

[0015] 2. The present invention utilizes the deposition and acidification properties of chlorogenic acid to improve the connection stability of polydopamine and polyvinyl alcohol on micron silicon and enhance the stability of the intermediate porous structure.

[0016] 3. The present invention utilizes the multi-group activity of polydopamine and its attraction and deposition characteristics for polyvinyl alcohol to form a polyvinyl alcohol film on the surface of polydopamine. After constant temperature treatment and carbonization treatment, not only is the polyvinyl alcohol converted into a conductive double conjugated system polymer, but the polymer can also form a porous carbon-based material, thereby satisfying the compression space while improving the conductivity of the polymer. DETAILED DESCRIPTION

[0017] The present invention is described in detail with reference to the embodiments, but no limitation is imposed on the claims of the present invention.

[0018] Example 1

[0019] A method for preparing a multi-level sub-micron silicon negative electrode material comprises the following steps:

[0020] Step 1, put micron silicon into ethanol aqueous solution and stir for 20 minutes, filter and dry, add to hydrochloric acid solution and stir evenly to obtain acid-washed micron silicon, then add the acid-washed micron silicon into chlorogenic acid solution and ultrasonicate for 20 minutes, filter and dry to obtain chlorogenic acid-wrapped micron silicon; the mass ratio of the micron silicon to the ethanol aqueous solution is 1:3, the volume proportion of ethanol in the ethanol aqueous solution is 50%, the stirring speed is 200r / min, the drying temperature is 80°C, the pH of the hydrochloric acid solution is 4, and the mass ratio of the hydrochloric acid solution to the micron silicon is 2:1, the stirring speed for uniform stirring is 300r / min, the chlorogenic acid solution is chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 100g / L, the frequency of the ultrasound is 70kHz, and the temperature is 10°C; the drying temperature is 80°C;

[0021] Step 2, add dopamine and ethyl cellulose to ether and stir evenly, then add chlorogenic acid-wrapped micron silicon and drop a small amount of distilled water, ultrasonicate for 10 minutes, stir for 20 minutes, filter and dry to obtain coated particles, the mass ratio of dopamine to ethyl cellulose is 1:10, the concentration of ethyl cellulose in ether is 200g / L, the stirring speed for uniform stirring is 100r / min, the concentration of chlorogenic acid-wrapped micron silicon in ether is 50g / L, the frequency of the ultrasound is 70kHz, the temperature is 5°C; the stirring speed is 200r / min, and the drying temperature is 30°C;

[0022] Step 3: spraying sodium hydroxide solution onto the surface of the coated particles and standing at a constant temperature for 2 hours to obtain polydopamine-ethylcellulose-wrapped micron silicon. The pH of the sodium hydroxide solution is 10, and the spray volume is 0.2 mL / cm 2 , the constant temperature static temperature is 50°C;

[0023] Step 4, putting polydopamine-ethylcellulose wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine wrapped micron silicon, then putting it into polyvinyl alcohol phenol solution and standing at a constant temperature for 20 minutes, filtering and freeze-drying to obtain in-situ porous coated micron silicon, the mass ratio of the polydopamine-ethylcellulose wrapped micron silicon to the ether is 1:6, the stirring speed for uniform stirring is 200r / min, and the drying temperature is 30°C; the mass ratio of polyvinyl alcohol to phenol in the polyvinyl alcohol phenol solution is 1:12, the mass ratio of porous polydopamine wrapped micron silicon to polyvinyl alcohol is 10:1, the constant temperature standing temperature is 80°C, and the freeze-drying temperature is -10°C;

[0024] Step 5, mixing ether and water and stirring them thoroughly to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, and then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid, wherein the mass ratio of the ether to water is 10:1, the stirring speed is 100 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is 4:0.3:1, the concentration of the ethyl cellulose in the ether is 20%, and the stirring speed is 300 r / min;

[0025] Step 6: immerse the in-situ porous coated micron silicon in the viscous liquid and stir for 2 minutes, filter and dry, spray the surface with pyrrole monomer ether solution, and acid self-polymerize after deposition to obtain polypyrrole-wrapped micron silicon, wherein the mass ratio of the in-situ porous coated micron silicon to the viscous liquid is 1:5, the stirring speed is 800 r / min, the drying temperature is 20°C, the mass ratio of the pyrrole monomer in the pyrrole monomer ether solution to the ether is 1:2, and the deposition amount is 1 mL / cm 2 The acidic self-polymerization solvent is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 40°C;

[0026] Step 7, subjecting the polypyrrole-wrapped micron silicon to a constant temperature treatment for 30 minutes, and subjecting the carbonization treatment to a multi-level sub-micron silicon lithium battery negative electrode material, wherein the constant temperature treatment temperature is 250° C.; the carbonization treatment is performed under a nitrogen atmosphere, and the carbonization temperature is 500° C. The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as a core, a porous polyvinyl alcohol condensation polymer as a connecting layer, and a polypyrrole-based carbon layer as a carbon shell, and the polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

[0027] Example 2

[0028] A method for preparing a multi-level sub-micron silicon negative electrode material comprises the following steps:

[0029] Step 1, put micron silicon into ethanol aqueous solution and stir for 30 minutes, filter and dry, add to hydrochloric acid solution and stir evenly to obtain acid-washed micron silicon, then add the acid-washed micron silicon to chlorogenic acid solution for ultrasonic 30 minutes, filter and dry to obtain chlorogenic acid-wrapped micron silicon; the mass ratio of the micron silicon to the ethanol aqueous solution is 1:5, the volume proportion of ethanol in the ethanol aqueous solution is 70%, the stirring speed is 400r / min, the drying temperature is 90°C, the pH of the hydrochloric acid solution is 5, and the mass ratio of the hydrochloric acid solution to the micron silicon is 3:1, the stirring speed for uniform stirring is 500r / min, the chlorogenic acid solution is chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 200g / L, the frequency of the ultrasound is 90kHz, and the temperature is 20°C; the drying temperature is 90°C;

[0030] Step 2, add dopamine and ethyl cellulose to ether and stir evenly, then add chlorogenic acid-wrapped micron silicon and drop a small amount of distilled water, ultrasonicate for 20 minutes, stir for 30 minutes, filter and dry to obtain coated particles, the mass ratio of dopamine to ethyl cellulose is 1:12, the concentration of ethyl cellulose in ether is 400g / L, the stirring speed for uniform stirring is 200r / min, the concentration of chlorogenic acid-wrapped micron silicon in ether is 100g / L, the frequency of the ultrasound is 90kHz, the temperature is 10°C; the stirring speed is 400r / min, and the drying temperature is 40°C;

[0031] Step 3: spraying sodium hydroxide solution onto the surface of the coated particles and standing at a constant temperature for 3 hours to obtain polydopamine-ethylcellulose-wrapped micron silicon. The pH of the sodium hydroxide solution is 11, and the spray volume is 0.4 mL / cm 2 , the constant temperature static temperature is 60°C;

[0032] Step 4, putting polydopamine-ethylcellulose wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine wrapped micron silicon, then putting it into polyvinyl alcohol phenol solution and standing at a constant temperature for 30 minutes, filtering and freeze-drying to obtain in-situ porous coated micron silicon, the mass ratio of the polydopamine-ethylcellulose wrapped micron silicon to the ether is 1:8, the stirring speed for uniform stirring is 400r / min, and the drying temperature is 40°C; the mass ratio of polyvinyl alcohol to phenol in the polyvinyl alcohol phenol solution is 1:15, the mass ratio of porous polydopamine wrapped micron silicon to polyvinyl alcohol is 10:1.3, the constant temperature standing temperature is 90°C, and the freeze-drying temperature is -10°C;

[0033] Step 5, mixing ether and water and stirring them thoroughly to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, and then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid, wherein the mass ratio of the ether to water is 15:1, the stirring speed is 200 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is 5:0.5:1, the concentration of the ethyl cellulose in the ether is 25%, and the stirring speed is 500 r / min;

[0034] Step 6: immerse the in-situ porous coated micron silicon in the viscous liquid and stir for 4 minutes, filter and dry, spray the surface with pyrrole monomer ether solution, and acid self-polymerize after deposition to obtain polypyrrole-wrapped micron silicon, wherein the mass ratio of the in-situ porous coated micron silicon to the viscous liquid is 1:8, the stirring speed is 1000 r / min, the drying temperature is 30°C, the mass ratio of the pyrrole monomer in the pyrrole monomer ether solution to the ether is 1:3, and the deposition amount is 1.5 mL / cm 2 The acidic self-polymerization solvent is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 50°C;

[0035] Step 7, the polypyrrole-wrapped micron silicon is subjected to a constant temperature treatment for 60 minutes, and a multi-level sub-micron silicon lithium battery negative electrode material is obtained by carbonization treatment, wherein the temperature of the constant temperature treatment is 260° C.; the carbonization treatment is carried out in a nitrogen atmosphere, and the carbonization temperature is 520° C. The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as the core, a porous polyvinyl alcohol condensation polymer as the connecting layer, and a polypyrrole-based carbon layer as the carbon shell, and the polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

[0036] Example 3

[0037] A method for preparing a multi-level sub-micron silicon negative electrode material comprises the following steps:

[0038] Step 1, put the micron silicon into an ethanol aqueous solution and stir for 25 minutes, filter and dry, add it to a hydrochloric acid solution and stir evenly to obtain acid-washed micron silicon, then add the acid-washed micron silicon to a chlorogenic acid solution and ultrasonicate for 25 minutes, filter and dry to obtain chlorogenic acid-wrapped micron silicon; the mass ratio of the micron silicon to the ethanol aqueous solution is 1:4, the volume proportion of ethanol in the ethanol aqueous solution is 60%, the stirring speed is 300r / min, the drying temperature is 85°C, the pH of the hydrochloric acid solution is 5, and the mass ratio of the hydrochloric acid solution to the micron silicon is 3:1, the stirring speed for uniform stirring is 400r / min, the chlorogenic acid solution is a chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 150g / L, the frequency of the ultrasound is 80kHz, and the temperature is 15°C; the drying temperature is 85°C;

[0039] Step 2, add dopamine and ethyl cellulose to ether and stir evenly, then add chlorogenic acid-wrapped micron silicon and drop a small amount of distilled water, ultrasonicate for 15 minutes, stir for 25 minutes, filter and dry to obtain coated particles, the mass ratio of dopamine to ethyl cellulose is 1:11, the concentration of ethyl cellulose in ether is 300g / L, the stirring speed for uniform stirring is 150r / min, the concentration of chlorogenic acid-wrapped micron silicon in ether is 80g / L, the frequency of ultrasound is 80kHz, the temperature is 8°C; the stirring speed is 300r / min, and the drying temperature is 35°C;

[0040] Step 3: spraying sodium hydroxide solution onto the surface of the coated particles and standing at a constant temperature for 3 hours to obtain polydopamine-ethylcellulose-wrapped micron silicon. The pH of the sodium hydroxide solution is 10, and the spray volume is 0.3 mL / cm 2 , the constant temperature static temperature is 55°C;

[0041] Step 4, putting polydopamine-ethylcellulose wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine wrapped micron silicon, then putting it into polyvinyl alcohol phenol solution and standing at a constant temperature for 25 minutes, filtering and freeze-drying to obtain in-situ porous coated micron silicon, the mass ratio of the polydopamine-ethylcellulose wrapped micron silicon to the ether is 1:7, the stirring speed for uniform stirring is 300r / min, and the drying temperature is 35°C; the mass ratio of polyvinyl alcohol to phenol in the polyvinyl alcohol phenol solution is 1:14, the mass ratio of porous polydopamine wrapped micron silicon to polyvinyl alcohol is 10:1, the constant temperature standing temperature is 85°C, and the freeze-drying temperature is -10°C;

[0042] Step 5, mixing ether and water and stirring them thoroughly to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, and then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid, wherein the mass ratio of the ether to water is 12:1, the stirring speed is 150 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is 5:0.4:1, the concentration of the ethyl cellulose in the ether is 23%, and the stirring speed is 400 r / min;

[0043] Step 6: immerse the in-situ porous coated micron silicon in the viscous liquid and stir for 3 minutes, filter and dry, spray the surface with pyrrole monomer ether solution, and acid self-polymerize after deposition to obtain polypyrrole-wrapped micron silicon, wherein the mass ratio of the in-situ porous coated micron silicon to the viscous liquid is 1:7, the stirring speed is 900 r / min, the drying temperature is 25°C, the mass ratio of the pyrrole monomer in the pyrrole monomer ether solution to the ether is 1:2, and the deposition amount is 1.3 mL / cm 2The acidic self-polymerization solvent is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 45°C;

[0044] Step 7, the polypyrrole-wrapped micron silicon is subjected to a constant temperature treatment for 50 minutes, and a multi-level sub-micron silicon lithium battery negative electrode material is obtained by carbonization treatment, wherein the temperature of the constant temperature treatment is 255° C.; the carbonization treatment is carried out in a nitrogen atmosphere, and the carbonization temperature is 510° C. The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as the core, a porous polyvinyl alcohol condensation polymer as the connecting layer, and a polypyrrole-based carbon layer as the carbon shell, and the polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

[0045] Comparative Example 1

[0046] A method for preparing a multi-level sub-micron silicon negative electrode material comprises the following steps:

[0047] Step 1, put the micron silicon into an ethanol aqueous solution and stir for 25 minutes, filter and dry, add it to a hydrochloric acid solution and stir evenly to obtain acid-washed micron silicon, then add the acid-washed micron silicon to a chlorogenic acid solution and ultrasonicate for 25 minutes, filter and dry to obtain chlorogenic acid-wrapped micron silicon; the mass ratio of the micron silicon to the ethanol aqueous solution is 1:4, the volume proportion of ethanol in the ethanol aqueous solution is 60%, the stirring speed is 300r / min, the drying temperature is 85°C, the pH of the hydrochloric acid solution is 5, and the mass ratio of the hydrochloric acid solution to the micron silicon is 3:1, the stirring speed for uniform stirring is 400r / min, the chlorogenic acid solution is a chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 150g / L, the frequency of the ultrasound is 80kHz, and the temperature is 15°C; the drying temperature is 85°C;

[0048] Step 2, add dopamine and ethyl cellulose to ether and stir evenly, then add chlorogenic acid-wrapped micron silicon and drop a small amount of distilled water, ultrasonicate for 15 minutes, stir for 25 minutes, filter and dry to obtain coated particles, the mass ratio of dopamine to ethyl cellulose is 1:11, the concentration of ethyl cellulose in ether is 300g / L, the stirring speed for uniform stirring is 150r / min, the concentration of chlorogenic acid-wrapped micron silicon in ether is 80g / L, the frequency of ultrasound is 80kHz, the temperature is 8°C; the stirring speed is 300r / min, and the drying temperature is 35°C;

[0049] Step 3: spraying sodium hydroxide solution onto the surface of the coated particles and standing at a constant temperature for 3 hours to obtain polydopamine-ethylcellulose-wrapped micron silicon. The pH of the sodium hydroxide solution is 10, and the spray volume is 0.3 mL / cm 2 , the constant temperature static temperature is 55°C;

[0050] Step 4, putting polydopamine-ethylcellulose wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine wrapped micron silicon, freeze-drying to obtain in-situ porous coated micron silicon, the mass ratio of the polydopamine-ethylcellulose wrapped micron silicon to ether is 1:7, the stirring speed for uniform stirring is 300r / min, and the drying temperature is 35°C; the mass ratio of polyvinyl alcohol to phenol in the polyvinyl alcohol-phenol solution is 1:14, the mass ratio of porous polydopamine wrapped micron silicon to polyvinyl alcohol is 10:1, the constant temperature standing temperature is 85°C, and the freeze-drying temperature is -10°C;

[0051] Step 5, mixing ether and water and stirring them thoroughly to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, and then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid, wherein the mass ratio of the ether to water is 12:1, the stirring speed is 150 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is 5:0.4:1, the concentration of the ethyl cellulose in the ether is 23%, and the stirring speed is 400 r / min;

[0052] Step 6: immerse the in-situ porous coated micron silicon in the viscous liquid and stir for 3 minutes, filter and dry, spray the surface with pyrrole monomer ether solution, and acid self-polymerize after deposition to obtain polypyrrole-wrapped micron silicon, wherein the mass ratio of the in-situ porous coated micron silicon to the viscous liquid is 1:7, the stirring speed is 900 r / min, the drying temperature is 25°C, the mass ratio of the pyrrole monomer in the pyrrole monomer ether solution to the ether is 1:2, and the deposition amount is 1.3 mL / cm 2 The acidic self-polymerization solvent is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 45°C;

[0053] Step 7, the polypyrrole-wrapped micron silicon is subjected to a constant temperature treatment for 50 minutes, and a multi-level sub-micron silicon lithium battery negative electrode material is obtained by carbonization treatment, wherein the temperature of the constant temperature treatment is 255° C.; the carbonization treatment is carried out in a nitrogen atmosphere, and the carbonization temperature is 510° C. The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as the core, a porous polyvinyl alcohol condensation polymer as the connecting layer, and a polypyrrole-based carbon layer as the carbon shell, and the polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

[0054] Comparative Example 2

[0055] The preparation method of Comparative Example 2 is the same as that of Comparative Example 1, except that the dopamine in Comparative Example 1 is replaced by conductive carbon black and dopamine in a mass ratio of 10:1.

[0056] Performance Testing

[0057] The negative electrode materials in Examples 1-3 and Comparative Examples 1-2 are prepared to form negative electrode sheets, and the preparation method of the negative electrode sheets is: carboxymethyl cellulose is added into water and stirred evenly to form a glue solution, and then the negative electrode material and lithium titanate are added in sequence to mix into a slurry, and the slurry is coated on the surface of a conductive substrate, and dried to obtain a negative electrode sheet, wherein the mass ratio of carboxymethyl cellulose, lithium titanate, and negative electrode material is 1:0.5:10, the mass ratio of carboxymethyl cellulose to water is 1:40, the drying temperature is 110°C, and the drying time is 12h.

[0058] The negative electrode sheets prepared from the negative electrode materials prepared in Examples 1-3 and Comparative Example 1 were used as working electrodes and button cells were assembled with LiPF6 / DMC+EC+DEC (1:1:1) as the electrolyte. The charge and discharge were carried out with a cut-off voltage of 0.01-1.5V. The first charge specific capacity, first coulomb efficiency, 50-week cycle retention rate, and 0.3C / 0.1C capacity retention rate were measured. The test results are as follows.

[0059]

[0060] The above test data show that the micron silicon lithium battery negative electrode material prepared by this method has good performance, and performs well in the first charge specific capacity, first coulomb efficiency, 50-week cycle retention rate, and 0.3C / 0.1C capacity retention rate.

[0061] It is understood that the above specific description of the present invention is only used to illustrate the present invention and is not limited to the technical solutions described in the embodiments of the present invention. Those skilled in the art should understand that the present invention can still be modified or replaced by equivalents to achieve the same technical effects; as long as the use requirements are met, they are within the protection scope of the present invention.

Claims

1. A method for preparing a multi-level sub-micron silicon negative electrode material, characterized in that: The preparation method comprises the following steps: Step 1, placing micron silicon in an ethanol aqueous solution and stirring for 20-30 minutes, filtering and drying, adding to a hydrochloric acid solution and stirring evenly to obtain acid-washed micron silicon, then adding the acid-washed micron silicon to a chlorogenic acid solution and ultrasonicating for 20-30 minutes, filtering and drying to obtain chlorogenic acid-coated micron silicon; Step 2, adding dopamine and ethyl cellulose to ether and stirring evenly, then adding chlorogenic acid-wrapped micron silicon and dropping a small amount of distilled water, ultrasonicating for 10-20 minutes, stirring for 20-30 minutes, filtering and drying to obtain coated particles; Step 3, spraying sodium hydroxide solution onto the surface of the coated particles, and standing at a constant temperature for 2-3 hours to obtain polydopamine-ethylcellulose-wrapped micron silicon; Step 4, putting the polydopamine-ethylcellulose-wrapped micron silicon into ether and stirring evenly, filtering and drying to obtain porous composite polydopamine-wrapped micron silicon, then putting it into polyvinyl alcohol phenol solution and standing at a constant temperature for 20-30 minutes, filtering and freeze-drying to obtain in-situ porous coated micron silicon; Step 5, mixing ether and water and stirring them thoroughly to form a layered liquid, extracting the ether layer to obtain an aqueous ether liquid, and then adding pyrrole monomer, dopamine and ethyl cellulose, and stirring to obtain a viscous liquid; Step 6, immersing the in-situ porous coated micron silicon in the viscous liquid and stirring for 2-4 minutes, spraying the surface with pyrrole monomer ether solution after filtering and drying, and acid self-polymerizing after deposition to obtain polypyrrole-coated micron silicon; Step 7, subjecting the polypyrrole-wrapped micron silicon to a constant temperature treatment for 30-60 minutes, and obtaining a multi-level sub-micron silicon lithium battery negative electrode material through a carbonization treatment.

2. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The mass ratio of micron silicon to ethanol aqueous solution in step 1 is 1:(3-5), the volume proportion of ethanol in the ethanol aqueous solution is 50-70%, the stirring speed is 200-400r / min, the drying temperature is 80-90°C, the pH of the hydrochloric acid solution is 4-5, and the mass ratio of the hydrochloric acid solution to micron silicon is (2-3):1, the stirring speed for uniform stirring is 300-500r / min, the chlorogenic acid solution is a chlorogenic acid ethanol solution, and the concentration of chlorogenic acid in ethanol is 100-200g / L, the frequency of the ultrasound is 70-90kHz, and the temperature is 10-20°C; the drying temperature is 80-90°C.

3. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The mass ratio of dopamine to ethyl cellulose in step 2 is 1:(10-12), the concentration of ethyl cellulose in ether is 200-400 g / L, the stirring speed for uniform stirring is 100-200 r / min, the concentration of chlorogenic acid-encapsulated microsilicon in ether is 50-100 g / L, the frequency of the ultrasound is 70-90 kHz, the temperature is 5-10°C; the stirring speed is 200-400 r / min, and the drying temperature is 30-40°C.

4. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The pH of the sodium hydroxide solution in step 3 is 10-11, and the spray volume is 0.2-0.4 mL / cm 2 The constant temperature standing temperature is 50-60°C.

5. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The mass ratio of polydopamine-ethylcellulose wrapped micro-silicon to ether in the step 4 is 1:(6-8), the stirring speed for uniform stirring is 200-400r / min, and the drying temperature is 30-40°C; the mass ratio of polyvinyl alcohol to phenol in the polyvinyl alcohol-phenol solution is 1:(12-15), the mass ratio of porous polydopamine wrapped micro-silicon to polyvinyl alcohol is 10:(1-1.3), the constant temperature standing temperature is 80-90°C, and the freeze-drying temperature is -10°C.

6. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The mass ratio of diethyl ether to water in step 5 is (10-15):1, the stirring speed is 100-200 r / min, the mass ratio of the pyrrole monomer, dopamine and ethyl cellulose is (4-5):(0.3-0.5):1, the concentration of ethyl cellulose in diethyl ether is 20-25%, and the stirring speed is 300-500 r / min.

7. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The mass ratio of the in-situ porous coated micron silicon to the viscous liquid in step 6 is 1:(5-8), the stirring speed is 800-1000r / min, the drying temperature is 20-30°C, the mass ratio of the pyrrole monomer to the ether in the pyrrole monomer ether solution is 1:(2-3), and the deposition amount is 1-1.5mL / cm 2 The acidic self-polymerization solvent is hydrogen peroxide containing hydrochloric acid, the mass concentration of hydrogen peroxide is 30%, the pH is 5, and the temperature is 40-50°C.

8. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The temperature of the constant temperature treatment in step 7 is 250-260°C; the carbonization treatment is carried out in a nitrogen atmosphere, and the carbonization temperature is 500-520°C.

9. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 1, characterized in that: The multi-level sub-micron silicon lithium battery negative electrode material has micron silicon as the core, a polyvinyl alcohol condensation polymer with a porous structure as the connecting layer, and a polypyrrole-based carbon layer as the carbon shell.

10. The method for preparing the multi-level sub-micron silicon negative electrode material according to claim 9, characterized in that: The polyvinyl alcohol condensation polymer inside the connecting layer has a porous structure.

Citation Information

Patent Citations

  • Preparation method of micron silicon negative electrode for lithium ion batteries

    CN106684335A

  • Micron silicon composite material and preparation method and application thereof

    CN114267839A

  • Sodium-ion battery positive electrode material, preparation method thereof and sodium-ion battery

    CN115312782A

  • Preparation of micron-scale silicon-carbon composite negative electrode material and application of micron-scale silicon-carbon composite negative electrode material in lithium ion battery

    CN117976861A

  • Preparation method of micron silicon-carbon negative electrode material and micron silicon-carbon negative electrode plate

    CN118367134A